Potensi Logam Tanah Jarang Wilayah Toboali Bangka Selatan - Marwan Asof; Rosihan Pebrianto; Edwin Harsiga; Syarifudin Syarifudin (PROMINE, 2022)
The Bangka Belitung Islands are an area traversed by the tin belt of Southeast Asia. This tin belt carries tin-bearing minerals and is associated with rare earth metals (LTJ). Toboali is a sub-district in South Bangka Regency. The exploration phase carried out by PT Timah made it possible to identify rare earth elements at the same time. Samples were taken using a sonic drilling machine to a depth of 5 meters. Every 1 meter 1 sample is taken which is put into a transparent plastic and labeled. There were 100 samples tested in the laboratory using X-RD (X-ray Diffraction), XRF, Scanning Electron Microscope (SEM) and Inductively Coupled Plasma (ICP). From the results of observations and laboratory analysis, it is known that there are 5 LTJ elements that are most dominantly found in each sample, namely Serium (Ce) an average of 61.92 ppm, Yttrium (Y) an average of 34.6 ppm, Lanthanum (La) an average of 27.55 ppm, Neodymium (Nd) an average of 27.55 and Samarium (Sm) an average of 2.82. Sampling or exploration using a sonic drilling machine needs to be evaluated to get a better level of sample and data accuracy